P2X7 Receptor Deficiency Ameliorates STZ-induced Cardiac Damage and Remodeling Through PKCβ and ERK - Huang, Shanjun; Wang, Weiqi; Li, Li; Wang, Ting; Zhao, Yihan; Lin, Ya; Huang, Weijian; Wang, Yonghua; Huang, Zhouqing (Frontiers in Cell and Developmental Biology, 2021)
Diabetic cardiomyopathy (DCM) is a complication of diabetes mellitus which result in cardiac remodeling and subsequent heart failure. However, the role of P2X7R in DCM has yet to be elucidated. The principal objective of this study was to investigate whether P2X7R participates in the pathogenesis of DCM. In this study, the C57BL/6 diabetic mouse model was treated with a P2X7R inhibitor (A438079). Cardiac dysfunction and remodeling were attenuated by the intraperitoneal injection of A438079 or P2X7R deficiency. In vitro, A438079 reduced high glucose induced cell damage in H9c2 cells and primary rat cardiomyocytes. Furthermore, HG/STZ-induced P2X7R activation mediated downstream protein kinase C-β (PKC-β) and extracellular regulated protein kinases (ERK) activation. This study provided evidence that P2X7R plays an important role in the pathogenesis of STZ-induced diabetic cardiac damage and remodeling through the PKC-β/ERK axis and suggested that P2X7R might be a potential target in the treatment of diabetic cardiomyopathy.